Predicting the life of textile materials as automotive car seat fabrics / Mohamad Faizul Yahya and Abbas Deghami - Yahya, Mohamad Faizul; Deghami, Abbas (Faculty of Applied Sciences, 2004)
This paper describes the analysis of two important properties for car seat fabrics namely abrasion and tensile. The data obtained from the tests on these properties were reviewed and durability and energy coefficient (DEC) graphs were constructed for further analysis. Good relationship was found especially in warp direction. The understanding of the graph could become useful tool for fabric engineering and cost control for fabric manufacturing.